2012
DOI: 10.1097/ijg.0b013e31820719c8
|View full text |Cite
|
Sign up to set email alerts
|

Change in Intraocular Pressure Measurement After Myopic LASEK

Abstract: All tonometry methods measured a significant, but low, reduction of IOP 3 and 6 months after LASEK. Further change in visual acuity and IOP measurements between 3 and 6 months suggest a still ongoing postoperative process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…A further study found the difference in preoperative and postoperative GAT measurements to be greater than in DCT measurements from eyes undergoing myopic LASEK, which is again consistent with the results of our study 12. Based on the results of the present study as well as previous ones, it seems that substantial reduction in postoperative central corneal thickness causes a significant underestimation of intraocular pressure measurement by GAT, whereas measurements obtained by DCT are apparently unaffected.…”
Section: Discussionsupporting
confidence: 92%
“…A further study found the difference in preoperative and postoperative GAT measurements to be greater than in DCT measurements from eyes undergoing myopic LASEK, which is again consistent with the results of our study 12. Based on the results of the present study as well as previous ones, it seems that substantial reduction in postoperative central corneal thickness causes a significant underestimation of intraocular pressure measurement by GAT, whereas measurements obtained by DCT are apparently unaffected.…”
Section: Discussionsupporting
confidence: 92%
“…ART is a recently developed tonometry method [11,16,17]. It is slit-lamp-mounted, and based on resonance technique.…”
Section: Tonometry Methodsmentioning
confidence: 99%
“…Previous studies have reported that this tonometer can provide an overestimate in IOP values when compared to GAT [123][124][125]. Furthermore, it seems to be affected by CCT and corneal biomechanics [120,123,126]. Despite some advantages (repeatable and reliable measurements, no fluorescein is needed), the BioResonator ART has some drawbacks that may reduce its clinical usefulness, including: the need for a slit lamp, anesthetic and corneal contact, with sterilization issues; can be affected by various artifacts and measurement errors; moreover, its accuracy is influenced by the thickness and biomechanics of the cornea.…”
Section: Applanation Resonance Tonometrymentioning
confidence: 99%
“…Recently, two reviews on the micropulse diode laser trabeculoplasty were published [125,126]. The reviews were conducted in a similar manner to SLT; however, a subthreshold micropulse diode laser technique as used that split up a continuous laser beam into on-and-off pulses to enable in-between cooling, similar to the micropulse modality of retinal micropulse laser treatment.…”
Section: Future Perspectives and Alternatives Consideredmentioning
confidence: 99%